Formulao teorica de comportamento inteligente: Um modelo sugerido - Rowland, Thomas; Natalicio, Luiz F.S. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Education is seen as a behavioral science consisting of planned intervention into developmental sequence. Intelligent behavior is the objective of education; the purpose is behavior modification toward socially determined criteria. With a dyadic model, intelligent behavior is shown to be the result of the invariant processes of (a) reciprocal interaction between the organism and it’s genetic, internal, and external environments, (b) the acquisition of experience which involves transformation within the organism and (c) the development of central processes of control. The operational principle is seen as continuity-discontinuity in feedback from the organism environment interaction.